2012
DOI: 10.2514/1.56776
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Control of Combustion-Mode Transition in a Scramjet Engine

Abstract: A sidewall compression scramjet engine operated in two combustion modes under Mach 6 flight condition, weak-and intensive-combustion modes. The weak mode occurred below the overall fuel equivalence ratio (Φ) of around 0.4. Transition from the weak mode to the intensive mode occurred at Φ ~ 0.4, accompanied by a sudden increase in thrust. Mechanisms of the transition were numerically investigated in this study. Our simulations captured the sudden increase in thrust at the mode transition. In the weak mode, comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Finally, the intensive combustion with boundary layer separation around the fuel injector was attained. This mechanism was confirmed by Kouchi using 3‐dimensional computational simulation. Micka and Driscoll have observed 2 distinct combustion stabilization modes for ramjet operation, namely, the jet‐wake–stabilized and the cavity‐stabilized modes.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Finally, the intensive combustion with boundary layer separation around the fuel injector was attained. This mechanism was confirmed by Kouchi using 3‐dimensional computational simulation. Micka and Driscoll have observed 2 distinct combustion stabilization modes for ramjet operation, namely, the jet‐wake–stabilized and the cavity‐stabilized modes.…”
Section: Introductionmentioning
confidence: 60%
“…Sullins experimentally achieved the mode transition by increasing the combustor entrance total temperature. Through injecting different fuel flow rates, Takahashi et al and Kouchi et al distinguished 4 combustion modes, namely, blowout, weak combustion, strong combustion, and thermally choked. Turner and Smart investigated combustion modes by using 2 combustion chamber configurations with different lengths of constant area section for flight at Mach 8.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated the influencing factors [3][4][5][6] and control methods [7] of dual-mode supersonic combustors. Transition between the scram and ram modes is realized by changing the inflow condition, fuel scheme, and combustor design.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [16,17] numerically and experimentally analyzed the pressure of ram-to-scram transition under continuously changing inlet flow Mach number. Kouchi and Mitani [7] numerically and experimentally obtained different modes by changing the fuel equivalence ratio under fixed Mach number and found that the mode transition jumps because of changes in the flame stability mode and flame propagation mode.…”
Section: Introductionmentioning
confidence: 99%